Faktor-Faktor Yang Berhubungan Dengan Kejadian Ikterus Pada Bayi Baru Lahir Di RSU UMMI - Elsi Rahmadani; Marlin Sutrisna (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Jaundice is one of the contributors to infant morbidity in Indonesia because it can cause the baby's body to become weak and refuse to suck, increased muscle tone, stiff neck, muscle spasms, seizures, sensory disturbances, mental retardation, disability and even death. The purpose of this study was to determine Factors Related To Icterus Incident On Newborn Baby At Ummi Hospital. The method used is an analytical research design with a cross sectional approach. The sample in this study are 55 mothers who have newborn babies and chosen by using accidental sampling technique. This study uses SPSS with a chi-square bivariate statistical test. The results of the univariate analysis showed that most of the respondents were not LBW, most were not ABO incompatibility, the frequency of breastfeeding was more than 8 times and most were not jaundiced. The results of the bivariate analysis showed that there was a relationship between low birth weight, breastfeeding frequency, ABO incompatibility with the incidence of jaundice in newborns (p 0.000). Researchers suggest that Public Health Center is expected to provide information about health, especially about jaundice.